Financial Performance Analysis Using Liquidity, Solvency and Efficiency Ratios at PT. Bank Syariah Indonesia - Honi Karlina; Zela anggara (Yayasan Darussalam Bengkulu, 2022)
To assess the financial well-being of Bank Muamalat Indonesia, this study will use liquidity, solvency, and efficiency metrics. The research methodology used in this study is descriptive quantitative. A review of the liquidity, solvency, and efficiency ratios will help you understand the material you find while browsing through libraries and research papers. From 2019 to 2021, the data shows that the bank has a poor liquidity ratio, as seen from the Quick Ratio indicator, although the cash and loan-to-deposit ratios are good. However, the asset-to-loan ratio appears to be in good shape, based on Bank Indonesia's decision. Based on the primary ratio indicators, the solvency ratio is in a poor position in 2019 and 2020, while in 2021 it is in very good condition. The secondary risk ratio indicators for 2019-2021, when it appears to be in perfect health, support this. Based on the capital ratio indicator, the 2019-2020 period is considered unhealthy, but healthy for the 2021 period based on Bank Indonesia guidelines. The interest cost ratio and leverage multiplier indicators show that the efficiency ratio is more than 1.5, which is good news.